Correlation between 7P’s Marketing Mix and Historical Tourism Promotion of Chan Palace in Phitsanulok Province - Ketnoi, Chanchanit; Soontayatron, Somruthai (Academic Journal of Thailand National Sports University, 2018)
The purposeof this research was tostudythecorrelation between7P’s marketing mix and historical tourism promotion of Chan Palace, Phitsanulok province. The samples were 400 Thai tourists who travelled to Chan Palace,Phitsanulok province.This research adopted questionnaires inorder to study the correlation between correlation between 7p’s marketing mix and historical tourism promotion of Chan Palace in Phisanulok Province, as a main method for the data collection with IOC of 0.83 and coefficient alpha equal of 0.91. This study alsoapplied statistical data analyses withfrequency, percentage, meanand standard deviation. The data analysis of this research was also to test the Pearson product-moment correlation coefficient for evaluate relationship between variables. Results werefound that,Thai touristshaveattitudetowards7P’smarketingmix,overall, in high level (4.05). When considering in each item, Thai tourists had the highest level of attitude towards product, physical evidence and process, as well as high level of attitude towards people, place, price and promotion of 7P’s marketing mix. Furthermore, Thai tourists had overall high level of attitude towards historical tourism promotion of Chan Palace, Phitsanulok province (4.04). 7P’s marketing mix correlate with historical tourism promotion of Chan Palace, Phitsanulok province in high level with statistical significance at 0.00.